Penyusunan Manajemen Risiko TI Berdasarkan Cobit 2019 I&T Risk Focus Area Untuk Digitalisasi Fintechco - Azis, Abdul; Mulyana, Rahmat; Fauzi, Rokhman (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The rapid embrace of digital technology is visible in the Fintech industry as a born-digital company. Previous research identified the influence of IT governance (ITG) on organizational performance (OP), mediated by digital transformation (DT). However, more research is needed to understand how IT risk management works in Fintech's digitalization. This study uses Design Science Research (DSR) following ISACA's COBIT 2019 I&T Risk Focus Area. It looks at a case study in FintechCo, using interviews data and document triangulation. Solutions and plans are created based on the gaps found in seven components within FintechCo's three priorities: EDM03 Ensured Risk Optimization, APO12 Managed Risk, and MEA03 Managed Compliance with External Requirements resulting estimated capability improvement 0,8 (34,8%). This study helps us understand how to manage IT-related risks in organizational digitalization and offers practical insights for FintechCo's digitalization journey.